ARTIFICIAL INTELLIGENCE ON EFL IN VOCATIONAL HIGH SCHOOL: THE IMPACT OF TALKPAL.AI ON SPEAKING SKILL - Moh. Santoso; Khoirul Anwar; Nirwanto Maruf (University of Kuningan, 2025)
The integration of Artificial Intelligence (AI) into English as a Foreign Language (EFL) teaching has transformed how learners practice speaking, offering interactive, adaptive, and anxiety free environments. However, while AI tools have shown significant benefits in higher education, their use in vocational high schools where communication skills must align with industry specific needs remains underexplored. Most prior studies focus on university contexts, overlooking vocational learners who require workplace-oriented communication training. This study examines the impact of Talkpal.AI, an AI-based conversational platform, on vocational high school students’ English-speaking proficiency, focusing on fluency, accuracy, and communicative confidence. Using a mixed-methods design, seventy students were divided into experimental and control groups. The experimental group practiced with Talkpal.AI for six weeks, while the control group followed traditional instruction from teacher with same time. Quantitative result indicated a significant improvement in the experimental group’s speaking performance (p < .001, Cohen’s d = 1.45), particularly in fluency and pronunciation, confirming Talkpal.AI’s effectiveness in enhancing oral proficiency. Qualitative findings indicated that Talkpal.AI fostered confidence and reduced anxiety, yet students required extensive scaffolding to use the AI effectively for self-directed learning. Initial difficulties included interpreting feedback, sustaining motivation, and managing technical barriers. The study concludes that AI-assisted speaking practice enhances communicative competence when integrated with structured teacher guidance and reflective learning strategies, reinforcing AI’s potential as a pedagogical partner in vocational EFL context.